Triterpenes from the leaves of Glochidion obliquum - Thu, Vu Kim; Kieu Anh, Le Thi; Quang, Dang Ngoc; Thang, Nguyen Van; Tuan Anh, Hoang Le; Nhiem, Nguyen Xuan; Thuy Hang, Dan Thi; Minh, Chau Van; Kiem, Phan Van (Vietnam Journal of Chemistry, 2015)
Using combined chromatographic methods, six tritrerpenes, 5b,6b-epoxytaraxeran-3b-ol (1), 3β-hydroxyglutin-5-ene (2), friedelan-3-one (3), lupeol (4), glochidonol (5), and glochidone (6) were isolated from the methanol extract of the leaves of Glochidion obliquum Decne. Their structures were elucidated by 1D- and 2D-NMR spectra and in comparison with those reported in the literature. Of which, compound 1 was reported from nature for the first time.